Highly Interconnected Macroporous and Transparent Indium Tin Oxide Electrode. Issue 2 (27th November 2017) - Mierzwa, Maciej; Lamouroux, Emmanuel; Durand, Pierrick; Etienne, Mathieu
Abstract: A macroporous indium tin oxide (ITO) electrode has been obtained by electrospinning nanofibers from polyvinylpyrrolidone and ITO precursors on a fused silica substrate covered by polystyrene, followed by a heat treatment that induced a drastic modification in the material texture. The resulting electrode structure is consisting of highly interconnected nanofilaments of sizes between 70 and 170 nm. The electrode is robust, fixed to the substrate, transparent in the visible light region, and possesses excellent electrochemical properties in comparison to a planar ITO electrode, that is, improved reversibility with ferrocenedimethanol and greatly enhanced oxidation for ascorbic acid. SEM and XRD measurements confirm ITO formation. This porous ITO electrode can be modified electrochemically with mesostructured methylated silica and applied to a combined electrochemical and spectral detection of industrial dyes (methylene blue, Meldola's blue, and methylene green) from water. For methylene blue analysis, a linear range of detection between 20 nM and 2 μM and a limit of detection of 17 nM are observed. Finally, the spectroelectrochemical analysis of a solution with mixed dyes has been performed. Abstract : Making sense : A new electrospinning protocol for the preparation of indium tin oxide transparent porous electrode results in a unique nanofilament structure, allowing spectroelectrochemical analysis. As an example, it is applied in the electrochemical detection of methylene blue with a linear range of 20 nM–2 μM and a limit of detection at 17 nM. Spectroelectrochemical analysis of a solution with mixed dyes is also demonstrated.